Delirium in the course of dependence upon gamma-butyrolactone (GBL) - a case report - Łobejko, Łukasz; Machała, Piotr; Makarewicz, Agata; Karakuła-Juchnowicz, Hanna (Current Problems of Psychiatry, 2017)
Gamma-butyrolactone (GBL) is an organic chemical compound of the lactones group, undergoing biotransformation into gamma-hydroxybutyrate after the intake (GHB). Because of the easy access, low price and fast psychotropic effect, GBL is becoming increasingly popular substance having intoxicating effect. Taking of GBL causes dose-dependent euphoric, sedative, hypnotic effects. Its use can quickly lead to physical dependence with severe course of withdrawal syndromes. Withdrawal symptoms resemble those occurring in the course of addiction to alcohol or benzodiazepines. In some patients, delirium develops during substance withdrawal. There are described severe, life-threatening complications in the course of delirium in GBL-dependent patients. The management of withdrawal syndromes and delirium mainly involves administration of benzodiazepines. In this paper, we present a case of delirium in 24-year-old man addicted to GBL hospitalized in a psychiatric ward. Delirium in this patient went without complications and was successfully man-aged with diazepam and lorazepam.